2015
DOI: 10.1002/cb.1506
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Self‐Gifting Consumer Behaviour scale

Abstract: Self‐gifting consumer behaviour (SGCB) is on the rise as consumers seek reward and therapeutic benefits from their shopping experiences. SGCB is defined as personally symbolic, self‐communication through special indulgences, which tend to be premeditated and highly context bound. Prior research into the measurement of this growing behavioural phenomenon has been fragmented because of differences in conceptualisation. This research builds upon the prior literature and through a series of qualitative and quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 88 publications
0
51
0
1
Order By: Relevance
“…Internally, people can regulate their emotions, including sadness, for example, by modifying their interpretation of the emotion‐eliciting situation (cognitive change; Gross, ). However, people can also externally influence their emotions, for example, by engaging in hedonic purchasing and consumption (Atalay & Meloy, ; Kemp, Bui, & Grier, ; Kemp, Kennett‐Hensel, & Williams, ; Kemp & Kopp, ; Mortimer & Bougoure, ). In line with this account, Tice et al () showed that the effect of sadness on food indulgence is diminished when people are told that eating cannot improve their mood.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Internally, people can regulate their emotions, including sadness, for example, by modifying their interpretation of the emotion‐eliciting situation (cognitive change; Gross, ). However, people can also externally influence their emotions, for example, by engaging in hedonic purchasing and consumption (Atalay & Meloy, ; Kemp, Bui, & Grier, ; Kemp, Kennett‐Hensel, & Williams, ; Kemp & Kopp, ; Mortimer & Bougoure, ). In line with this account, Tice et al () showed that the effect of sadness on food indulgence is diminished when people are told that eating cannot improve their mood.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Self-service technology does not only give more control to customers, but it also reduces time, workload and operational cost of organizations (Ding et al, 2007;Mortimer et al, 2015). Therefore, benefits provided by SST, such as convenience, customization, and accessibility, create more value for customers than price (Fornell, 1992;Zeithaml et al, 1996;Mortimer et al, 2015;Demoulin and Djelassi, 2016). Customers use ATM, telephone banking, Internet banking and Mobile banking for saving time (Sarel and Marmorstein;Robertson et al, 2016;Kaushik and Rahman, 2015).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…For mobile banking, customer easily accesses all service. Ease of use function of SST also influences satisfaction of customer (Chen et al, 2009;Weijters et al, 2007;Mortimer et al, 2015). Difficult technology combined with complex processes can lead customer dissatisfaction (Meuter et al, 2003;.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Measures include the Yale-Brown Obsessive-Compulsive Scale–Shopping Version (Leite, Filomensky, Black, & Silva, 2014), Compulsive Buying Scale (Faber & O’Guinn, 1992), Edwards Compulsive Buying Scale-Revised (Edwards, 1993) and Richmond Compulsive Buying Scale (Ridgway, Kukar-Kinney, & Monroe, 2008). Other scales that have been employed to assess spending among non-clinical populations, such as the Impulse Buying Tendency Scale (Verplanken & Herabadi, 2001) or Self-Gifting Consumer Behavior Scale (Mortimer, Bougoure, & Fazal-E-Hasan, 2015), include items assessing spending in relation to emotion. However, none of these scales specifically assess spending as a means of coping with affective and social demands.…”
Section: Conceptual Framework: Coping Theorymentioning
confidence: 99%